Bentuk Pertunjukan Jaipongan Dalam Budaya Populer - Tubagus Mulyadi (Greget, 2013)
Jaipongan has become a part of the popular culture due to its dynamic movements, and its wide popularity has turned it into a consumptive culture which has the ability to make money. TheÂ presence of Jaipongan outside its own community is marked by its spread to a number of different areas, and also its merging or acculturation with other local art forms. Outside its own community, Jaipongan not only exists as a form of traditional dance or background dance but has also influenced other art forms, including music which now uses Jaipongan drum patterns.Keywords : Jaipongan, Popular Culture, and Consumptive.Â